Chiropractic: Is it Efficient in Treatment of Diseases? Review of Systematic Reviews - Alireza Salehi; Neda Hashemi; Mohammad Hadi Imanieh; Mahboobeh Saber (Shiraz University of Medical Sciences, 2015)
Abstract Chiropractic is a complementary medicine that has been growing increasingly in different countries over recent decades. It addresses the prevention, diagnosis and treatment of the neuromusculoskeletal system disorders and their effects on the whole body health. This study aims to evaluate the effectiveness of chiropractic in the treatment of different diseases. To gather data, scientific electronic databases, such as Cochrane, Medline, Google Scholar, and Scirus were searched and all systematic reviews in the field of chiropractic were obtained. Reviews were included if they were specifically concerned with the effectiveness of chiropractic treatment, included evidence from at least one clinical trial, included randomized studies and focused on a specific disease. The research data including the article's first author's name, type of disease, intervention type, number and types of research used, meta-analysis, number of participants, and overall results of the study, were extracted, studied and analyzed. Totally, 23 chiropractic systematic reviews were found, and 11 articles met the defined criteria. The results showed the influence of chiropractic on improvement of neck pain, shoulder and neck trigger points, and sport injuries. In the cases of asthma, infant colic, autism spectrum disorder, gastrointestinal problems, fibromyalgia, back pain and carpal tunnel syndrome, there was no conclusive scientific evidence. There is heterogeneity in some of the studies and also limited number of clinical trials in the assessed systematic reviews. Thus, conducting comprehensive studies based on more reliable study designs are highly recommended.